2009
DOI: 10.1186/1471-2164-10-644
|View full text |Cite
|
Sign up to set email alerts
|

A genomic glimpse of aminoacyl-tRNA synthetases in malaria parasite Plasmodium falciparum

Abstract: BackgroundPlasmodium parasites are causative agents of malaria which affects >500 million people and claims ~2 million lives annually. The completion of Plasmodium genome sequencing and availability of PlasmoDB database has provided a platform for systematic study of parasite genome. Aminoacyl-tRNA synthetases (aaRSs) are pivotal enzymes for protein translation and other vital cellular processes. We report an extensive analysis of the Plasmodium falciparum genome to identify and classify aaRSs in this organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 87 publications
(74 reference statements)
1
107
0
Order By: Relevance
“…The overall fold of PfTyrRS is typical of class I synthetases 3,4 and comprises a catalytic domain (residues 18-260, Rossmann fold) and an anti-codon-binding domain (residues 261-370). Human mitochondrial and malaria parasite apicoplastic TyrRS belong to bacterial lineage, whereas human cytoplasmic TyrRS and PfTyrRS belong to a separate eukaryotic group 6,29 ( Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The overall fold of PfTyrRS is typical of class I synthetases 3,4 and comprises a catalytic domain (residues 18-260, Rossmann fold) and an anti-codon-binding domain (residues 261-370). Human mitochondrial and malaria parasite apicoplastic TyrRS belong to bacterial lineage, whereas human cytoplasmic TyrRS and PfTyrRS belong to a separate eukaryotic group 6,29 ( Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that members of this enzyme family are quite adept at 'moonlighting' in terms of possessing extra capabilities that widen their biological attributes [5][6][7][8] . Studies have indicated that human tyrosyl-, tryptophanyl-and lysyl-tRNA synthetases can be secreted extracellularly and can mimic cytokines [5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations